Inconstitucionalidad del inciso final del artículo 483 del código orgánico integral penal - Sangucho Pulupa, Fausto Orlando (2017)
The present research work whose theme is "UNCONSTITUTIONALITY OF THE FINAL SECTION OF ARTICLE 483 OF THE CODEN INTEGRAL CRIMINAL INTEGRAL", is considered necessary the reform to this legal body, taking into consideration that in the absence of a current legislation violates the right to Legitimate defense of persons who in one way or another feel violated by granting impunity to the investigative agent who is immersed in an infraction or who has not prevented any due to the investigation that is being carried out. The implementation of the new Integrated Criminal Code has developed in Ecuador a new procedural criminal worldview that has dramatically changed both the dogmatic part as well as the catalog content of crimes and obviously procedural. Within this context has been implemented within the new code new figures that allow the administration of justice to proceed with greater speed for the processing of criminal proceedings, but also within the field of investigative actions of the Prosecutor and the Specialized Police, Changes have been evidenced that in our opinion only violate any constitutional or legal guarantee. This is the case of the second paragraph of Article 483 of the Integrated Criminal Code, where the rule exceeds all types of logic and grants impunity to the investigating agent who is immersed in an infraction or who has not prevented any because of the investigation that Is performing. The legal figure described in this rule generates legal insecurity because it is opposed to the very purpose of the criminal law of punishment and punishment to conduct that are opposed to the legal system and rights regimes enjoyed by citizens. The present thesis of Legal Investigation is structured as follows: In the first place a Conceptual Framework, which includes concepts and definitions of Sanctions, Penalties, Crimes and thus defining the experts so as to know their functions; A Doctrinal Framework, which covers the doctrines of writers and scholars on how to punish the agent who is in an operation and commits an infraction, then addresses a legal framework, which includes the analysis of the Constitution of the Republic Of Ecuador, the International Treaties and Conventions, the Integral Criminal Code, the Organic Code of Judicial Function and then we have a Comparative Legislation, since it served to me to carry out an analysis of the work of other countries and to extract the most positive . Secondly the research work comprises a field study in which surveys and interviews are developed to those who know the law in which they help me to determine or contrast the objectives and hypotheses raised. In the third place after the analysis of the field research, the conclusions and recommendations were made and finally a legal proposal necessary to solve the problem.